Market orientation and entrepreneurial success: mediating role of entrepreneurial learning intensity = Orientasi pasaran dan kejayaan keusahawanan: peranan pengantara intensiti pembelajaran keusahawanan - Juhdi, Noor Hasni; Tih, Sio Hong; Juhdi, Nurita (Universiti Kebangsaan Malaysia, 2015)
We addressed three research questions in this study: (1) What is the effect of market orientation on entrepreneurial success? (2) What is the relationship between market orientation and entrepreneurial learning intensity?; and (3) To what extent could entrepreneurial learning intensity enhance the relationship of market orientation – entrepreneurial success? Drawing on marketing and learning literature, we proposed that market orientation and entrepreneurial learning intensity infl uence entrepreneurial success. Based on resource-advantage theory, we believed that market orientation and entrepreneurial learning intensity are complementary resources in enhancing the capability of fi rms to gain competitive advantage. Through a simple mediation analysis, we posited that market orientation positively impact entrepreneurial success through entrepreneurial learning intensity. Based on data collected, by using questionnaire survey involving 125 owners of established small and medium-sized service enterprises around Malaysia, fi ndings confi rmed that market orientation, entrepreneurial learning intensity and entrepreneurial success are signifi cantly related. Entrepreneurial learning intensity partially mediated the relationship between market orientation and entrepreneurial success. Lastly, discussion and implications of the research fi ndings are provided in understanding the scenario of entrepreneurial success of small and medium-sized service enterprises in Malaysia.